Synthesis and Characterization of Lanthanides Mixed Ligand Complexes - N. Ghoshal, Monotosh (Asian Journal of Chemistry, 2010)
Mixed ligand complexes of La3+, Pr3+, Sm3+, Nd3+ and Dy3+ with nicotinic acid as primary ligand and thiourea as secondary ligands have been prepared and characterized on the basis of their element analysis, electronic and infrared spectra, thermal analysis and conductivity measurements. It has been observed that electronic and infrared spectra suggest interaction of metal ions with ligands and formation of bonds through nitrogen of pyridine ring in case of nicotinic acid and sulphur of thiourea. The thermal analysis of representative mixed complex shows loss of water around temperatures 170 and 121 °C. Above 154 °C the organic part of complex gets decomposed and complete loss of organic matter takes place at about 400 °C. At 530 °C formation of sesquei oxide of metal takes place. The conductivity measurements of the complex have shown that they are all non-electrolyte type.